Credit and Classification: The Impact of Industry Boundaries in Nineteenth-Century America - Ruef, Martin; Patterson, Kelly (Administrative Science Quarterly, 2009)
In this article, we examine how issues of multi-category membership (hybridity) were handled during the evolution of one of the first general systems of industrial classification in the United States, the credit rating schema of R. G. Dun and Company. Drawing on a repeated cross-sectional study of credit evaluations during the postbellum period (1870–1900), our empirical analyses suggest that organizational membership in multiple categories need not be problematic when classification systems themselves are emergent or in flux and when organizations avoid rare combinations or identities involving ambiguous components. As Dun's schema became institutionalized, boundaries between industries were more clearly defined and boundary violations became subject to increased attention and penalty by credit reporters. Our perspective highlights the utility of an evolutionary perspective and tests its implications for the salience of distinct mechanisms of hybridity.